Using CAST-test to investigate human specific hypersensitivity to the anthrax pathogen - D. G. Ponomarenko; E. L. Rakitina; M. V. Kostyuchenko; O. V. Logvinenko; A. G. Ryazanova; L Yu. Aksenova; N. P. Buravtseva; I. S. Tyumentseva; S. A. Kurcheva; A. N. Kulichenko (Медицинская иммунология, 2020)
We present the results of applying functional cytometric test of antigen-stimulated activation basophils to assess specific immunological reactivity in the people with anthrax, and immunized with anthrax vaccine. As a criterion for antigen-specific basophil activation, we measured expression of the CD63 membrane receptor, which reflects the process of anaphylactic basophil degranulation. To determine spontaneous and antigen-induced activation of basophils (CCR3+CD63+), a FlowCAST reagent kit (Buhlmann laboratories AG, Switzerland) was used. Anthraxin, an experimental anthrax allergen (a hydrolysate the Bacillus anthracis STI-1 strain), manufactured by the Stavropol Anti-Plague Institute, was used as a specific antigen. As based on clinical and experimental data, a threshold value of > 10% of anthraxin-activated (CCR3+CD63+) basophils was accepted for the in vitro immunodiagnostic CAST test, as a laboratory criterion for the subjects exhibiting specific immune response, i.e., IgE-mediated sensitization. It was shown that, in anthrax patients within one week after onset of the disease (3-7 days), a positive CAST result was obtained in 92.3% cases; the levels of specific basophil activation with anthraxin averaged 37.9% (12.01 ÷ 78.9%). Immunological examination of individuals three weeks (21 days) after vaccination against anthrax revealed CAST-positivity in all the vaccinated persons. Intensity of anthraxin-induced basophil activation the vaccinated subjects was ranged from 10.87 to 30.03%, averaging 17.86%. The overall values of spontaneous and specific activation ranged within 12.39 ÷ 41.46%. The study opens prospectives for implementation of basophil antigenic activation test in the Flow CAST format in diagnostics of anthrax and to identify specific immune rearrangements after vaccination in humans, as an index of actual vaccination rates. Usage of CAST test with anthraxin makes it possible to identify anthrax patients at the early stages (2-4 days after onset of the disease) including, among patients with an increased CCR3+CD63+ background values, evaluation of immunological efficiency in the cohorts at risk for vaccination. At the same time, it was found that a significant decrease in diagnostic sensitivity of CAST test could be observed in the patients immune to anthrax pathogen who received intensive antibacterial and pathogenetic therapy at the early stages of infection, including glucocorticosteroids (anti-inflammatory drugs) and desensitizing agents that inhibit the degree of hypersensitivity development and its expression.